2011
DOI: 10.1002/adma.201101410
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Oxide Thin‐Film Transistor

Abstract: The first ambipolar oxide‐based thin‐film transistor (TFT) using an SnO channel is presented, demonstrating operation of a complementary‐like inverter configured by two ambipolar SnO TFTs. Saturation mobilities of 0.8 and 5 × 10−4 cm2 V−1s−1 are obtained for the p‐channel and n‐channel modes, respectively, and the inverter shows a maximum voltage gain of 2.5. This is the first demonstration of a complementary‐like circuit using a single oxide semiconductor channel and provides an important step toward practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
227
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(241 citation statements)
references
References 29 publications
10
227
1
3
Order By: Relevance
“…In this case, the saturation field effect mobility was 0.81 cm 2 /Vs for the p-channel TFT and 5 × 10 −4 cm 2 /Vs for n-channel TFT. 26 Nayak et al has reported the p-channel and n-channel TFT in single step channel layer deposition. Either p-type SnO or n-type SnO 2 channel TFTs were formed depending on the method by which the gate insulator was deposited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the saturation field effect mobility was 0.81 cm 2 /Vs for the p-channel TFT and 5 × 10 −4 cm 2 /Vs for n-channel TFT. 26 Nayak et al has reported the p-channel and n-channel TFT in single step channel layer deposition. Either p-type SnO or n-type SnO 2 channel TFTs were formed depending on the method by which the gate insulator was deposited.…”
Section: Resultsmentioning
confidence: 99%
“…22,26,27 An important aspect of tin oxide material is that we can easily achieve ptype (SnO phase) and n-type (SnO 2 phase) conduction in this material. In this paper, we report the fabrication of both p-channel and nchannel TFTs starting from same source material.…”
mentioning
confidence: 99%
“…To realize complementary inverters, one can either combine an n-type TFT and a p-type TFT or use two ambipolar TFTs. A rail-to-rail output voltage behavior can be easily achieved in the former but hard to achieve in latter case because neither of the two ambipolar TFTs can be fully switched off [8,9,10,11]. The static current will also result in a static power consumption, which may be an issue in the case of large scale integration.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Both n-and p-type oxide semiconductors with excellent performance are necessary to develop oxide TFT-based circuits. However, most oxide semiconducting materials including zinc oxide (ZnO), indium gallium zinc oxide (IGZO), and indium zinc tin oxide (IZTO) show n-type properties.…”
Section: Introductionmentioning
confidence: 99%